An improved prediction of residual stresses and distortion in additive manufacturing - Mukherjee, T.; Zhang, W.; DebRoy, T. (Computational materials science, 2017)
[Display omitted] •Roles of variables and alloys on stresses and strains in 3D printing are studied.•Quality of residual stress and distortion modeling depends on temperature fields.•Flow of molten metal is considered to accurately calculate transient temperatures.•A finite element model calculates strain and residual stress from temperature field.•The results are helpful to make distortion free parts with low residual stresses. In laser assisted additive manufacturing (AM) an accurate estimation of residual stresses and distortion is necessary to achieve dimensional accuracy and prevent premature fatigue failure, delamination and buckling of components. Since many process variables affect AM, experimental measurements of residual stresses and distortion are time consuming and expensive. Numerical thermo-mechanical models can be used for their estimation, but the quality of calculations depends critically on the accurate transient temperature field which affects both the residual stresses and distortion. In this study, a well-tested, three-dimensional, transient heat transfer and fluid flow model is used to accurately calculate transient temperature field for the residual stress and distortion modeling. The calculated residual stress distributions are compared with independent experimental results. It is shown that the residual stresses can be significantly minimized by reducing the layer thickness during AM. Inconel 718 components are found to be more susceptible to delamination than Ti-6Al-4V parts because they encounter higher residual stresses compared to their yield strength.